Działania Unii Europejskiej na rzecz równouprawnienia kobiet i mężczyzn na rynku pracy - Pancer-Cybulska, Ewa (EU's Activities in Favour of Equality of Rights for Women and Men on the Labour Market, 2007)
The objective of the EU is to eliminate inequalities, counteraction against discriminate ich and support of equalities of men and women in all areas of life on the labour market and of it, The development of European integration causes changes in the range of rule of equality of men and women with reference to labour market. The paper presents the basic community law regulations and the most important activities for their implementation. Gaining objectives of equality policy is taking place thanks to wide range of instruments, mainly of legislative (directive guideline) and financial (programmes, initiatives, structural funds) character. Unfortunately, in spite of the positive assessments and opinions about applied instruments, it's impossible to speak about solving the problem of discrimination in respect of gender at the labour market. However, it can be stated that more effective ways of its overcoming are being searched for.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 37-52